Design optimization of a viscous micropump with two rotating cylinders for maximizing efficiency - Choi, Hyung-Il; Lee, Yongbin; Choi, Dong-Hoon; Maeng, Joo-Sung (Structural and multidisciplinary optimization, 2010)
This study presents design optimization of a viscous micropump with two rotating cylinders. The desired performance of the pump is to maximize the pumping efficiency while satisfying the constraints on flow rate and geometry. As a preliminary step, the effects of geometric configurations on the pumping performance are investigated by carrying out parametric studies using an unstructured grid Navier–Stokes method. Next, an optimization problem is formulated to determine the design variable values which maximize the pumping efficiency subject to the constraints. Then, a computational procedure, combining the analysis method with a sequential metamodel-based optimization method, is established to solve the optimization problem formulated. Finally, this procedure is applied to the optimization of ten design cases with varying flow rates specified. The optimization results demonstrate the effectiveness of the design optimization method presented in this study by showing that the efficiencies of the optimally designed micropumps are enhanced without any constraint violations.